“Are we going to do the most important things?”: Senator Muriel McQueen Fergusson, Feminist Identities, and the Royal Commission on the Status of Women - Campbell, Gail (Acadiensis, 2009)
Abstract Through the lens of an alternative narrative, this article traces the creation and evolution of the Royal Commission on the Status of Women in Canada, which was established during the long interval between the first and second waves of the women’s movement.  Based largely on the papers of Senator Muriel McQueen Fergusson, a leading member of a generation of women activists whose broader contributions to the women’s movement, while acknowledged, have rarely captured the imagination of scholars, it challenges scholars’ tendency to overlook the significance and essentialize the feminism of these inter-wave activists.